25
1) We must start by reminding the binomials. Since this question refers to a perfect square trinomial then we can write:
![(a-b)^2=a^2-2ab+b^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/wij5s4hl5c81m5e13tfkbmm8jk6ed6srgr.png)
2) Now we can look at the expression. Let's start by dividing that 10 by 2, since we have to write that -10x as 2 times the product of x and the other term:
![\begin{gathered} -(10)/(2)=5 \\ (x-5)^2=x^2-2(5)(x)+5^2=x^2-10x+25 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ferznrbb2ykoyk6seyda1tzss8uycano4b.png)
Note that the second term is 5²= 25
3) Hence, the answer is 25